Variability and effectiveness of comparator group interventions in smoking cessation trials: a systematic review and meta‐analysis. - Black, Nicola; Eisma, Maarten C.; Viechtbauer, Wolfgang; Johnston, Marie; West, Robert; Hartmann‐Boyce, Jamie; Michie, Susan; Bruin, Marijn (Addiction, 2020)
Aims: To examine variability and effectiveness of interventions provided to comparator (control) groups in smoking cessation trials. Methods: Systematic review with meta‐analysis of randomized controlled trials (RCTs) of behavioral interventions for smoking cessation, with or without stop‐smoking medication. We searched the Cochrane Tobacco Addiction Group Specialized Register for RCTs with objective outcomes measured at ≥ 6 months. Study authors were contacted to obtain comprehensive descriptions of their comparator interventions. Meta‐regression analyses examined the relationships of smoking cessation rates with stop‐smoking medication and behavior change techniques. Results: One hundred and four of 142 eligible comparator groups (n = 23 706) had complete data and were included in analyses. There was considerable variability in the number of behavior change techniques delivered [mean = 15.97, standard deviation (SD) = 13.54, range = 0–45] and the provision of smoking cessation medication (43% of groups received medication) throughout and within categories of comparator groups (e.g. usual care, brief advice). Higher smoking cessation rates were predicted by provision of medication [B = 0.334, 95% confidence interval (CI) = 0.030–0.638, P = 0.031] and number of behavior change techniques included (B = 0.020, 95% CI = 0.008–0.032, P < 0.001). Modelled cessation rates in comparator groups that received the most intensive support were 15 percentage points higher than those that received the least (23 versus 8%). Conclusions: Interventions delivered to comparator groups in smoking cessation randomized controlled trials vary considerably in content, and cessation rates are strongly predicted by stop‐smoking medication and number of behavior change techniques delivered.